Study on the Auditing Theory of Socialism with Chinese Characteristics, Revised Edition. - Liu, Jiayi (Wiley, 2015)
A comprehensive guide to China's public, private, and internal audit system Study on the Auditing Theory of Socialism with Chinese Characteristics provides a comprehensive overview of China's auditing practices. Recent years have seen the National Audit Office of China (CNAO) making remarkable headway not only in China by guaranteeing the healthy operation of the economy and society and improving national governance through government auditing, but also in the international arena by carrying out audits with the United Nations. With constant development in the practice, an audit theory with.